STUDI KESESUAIAN LAHAN DALAM RANGKA REVITALISASI TANAMAN APEL DI BATU, MALANG - , Sativandi Riza ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Apple trees became a nain comodity in Batu, Malang. However , the quality and production of Apples is no longer as good as before . Production decreases and is accompanied by the production of increasingly poor quality. Objective of this study is to (1) determine land suitability classes of apple trees on the different apple crop land conditions at different heights, (2) determine the effect of different height in the apple trees production, (3) determine land management conducted on each apples trees land in different heights. (4) determine the model to increase productivity and economic value. Observations based on the height difference, is at an altitude of 800 - 1000 meters above sea level, 1000 - 1600 meters above sea level , and 1600 - 2000 meters above sea levels. The locations of apple trees are selected into 2 groups, the productive apple trees land and non productive apple trees land. Physical data retrieval of land and soil samples was done by ground surveys and socio- economic data collection and management of land is done by using a questionaire. Physical land suitability analysis and economic use ALES program with Djaenuddin, et al (2003) as a refference. Apple crop land suitability classification is obtained that the apple crop at all locations S3 (marginally suitable). At location 1 (L01), 2 (L02), and 6 (L06) with the limiting factor are nutrient retention (S3,nr). While on location 3 (L03), 4 (L04), and 5 (L05) has a limiting factor erosion and nutrient retention (S3, eh/nr). There is an influence of the height of the apple crop productivity. This is evident with the highest productivity at location 3 (1600-2000 meters above sea levels) annualy + 1 tons. Apples of different land management at each height . Apple land at an altitude of 1200-2000 meters above sea level (L05 and L04) have high levels of management in accordance with the procedures for the cultivation of apples compared to apples land at an altitude of 800-1200 meters above sea level. Apple farm productivity in locations 4 and 5 ( L05 ) also have high productivity with 0.2 hectares of land and 100 trees . Formed models of revitalisastion such as Production = - 13.1 + 1.84 (Base Saturation) - 0.0149 (slope), with value of R2 = 0.935 and NPV = - 87,2 + 10,8(Production), R2=0,862.